Penerapan Rapid Application Development Pada Sistem Informasi Work Request Maintenance PT. NOK Indonesia - M Abi Zakaria; Hari Sugiarto - UBSI (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
Abstract - PT. NOK Indonesia which is located in Cikarang area needs a management system that enables faster and more accurate data related to the work request maintenance system, which until now has not been computerized. At this time the existing work request maintenance system at PT. NOK Indonesia is still done manually, starting from submitting a maintenance work request, recording the results of work requests that have been done, up to writing a work request report, making it possible for the work request process to experience inadequate data, as well as less efficient time. The method that I use in this research is Rapid Application Development as a flowchart of system development. The design of this information system is a solution that can solve the problems that exist in the management of maintenance work requests that exist in this company, as well as with a computerized system can achieve an activity that is more effective and efficient in supporting activities in managing work request maintenance. The results of this study are in the form of a work request maintenance information system that is expected to facilitate the process of managing the data.keywords: effective, information, methods, management, requests. Abstrak - PT. NOK Indonesia yang berlokasi di daerah cikarang membutuhkan sebuah sistem pengelolaan yang memungkinkan data lebih cepat dan lebih akurat yang berkaitan dengan sistem work request maintenance yang sampai saat ini belum terkomputerisasi. Pada saat ini sistem work request maintenance yang ada pada PT. NOK Indonesia masih dilakukan secara manual, dimulai dari mengajukan sebuah work request maintenance, mencatat hasil work request yang telah dikerjakan, sampai dengan menulis laporan work request, sehingga memungkinkan pada proses work request mengalami data yang kurang sesuai, serta waktu yang kurang efisien. Metode yang penulis gunakan dalam penelitian ini adalah Rapid Application Development sebagai alur dari pengembangan sistem. Perancangan sistem informasi ini merupakan sebuah solusi yang dapat memecahkan masalah yang ada pada pengelolaan work request maintenance yang ada pada perusahaan ini, serta dengan sistem yang terkomputerisasi dapat tercapai suatu kegiatan yang lebih efektif dan efisien dalam menunjang aktifitas pada pengelolaan work request maintenance. Hasil dari penelitian ini berupa sistem informasi work request maintenance yang diharapkan dapat memudahkan dalam proses pengelolaan data tersebut.Kata Kunci: efektif, informasi, metode, pengelolaan, request.